Governance Challenges at the Interface of Food Security and Biodiversity Conservation: A Multi-Level Case Study from Ethiopia - Jiren, Tolera Senbeto; Leventon, Julia; Jager, Nicolas W; Dorresteijn, Ine; Schultner, Jannik; Senbeta, Feyera; Bergsten, Arvid; Fischer, Joern (Environmental management, 2021)
Ensuring food security while also protecting biodiversity requires a governance system that can address intra- and intersectoral complexity. In this paper, we sought to explore the governance challenges surrounding food security and biodiversity conservation through an empirical study in Jimma zone, southwestern Ethiopia. We used bottom-up snowball sampling to identify stakeholders and then held semi-structured interviews with 177 stakeholders across multiple levels of governance. We also conducted 24 focus group discussions with local people. Data were transcribed and thematically analyzed for its contents. Challenges in the structure of institutions and policy incoherence were the key challenges identified for the governance of food security and biodiversity conservation. The challenges around institutional structure included incompatibilities of the nature of governing institutions with the complexity inherent within and between the two sectors examined. Incoherences in policy goals, instruments, and contradictions of policy output relative to the actual problems of food security and biodiversity further hampered effective governance of food security and biodiversity conservation. Notably, many of the challenges that influenced an individual sector also posed a challenge for the integrated governance of food security and biodiversity conservation, often in a more pronounced way. Based on our findings, we argue that governance in our case study area requires a more integrated and collaborative approach that pays attention to institutional interplay in order to ensure institutional fit and consistency across policy goals.
Keywords: Ethiopia; Etiopie; Policy incoherence; Integration; Institutional interplay; Food Security; Humans; biodiverzita; lidé; zachování přírodních zdrojů; Policy output; Conservation of Natural Resources; zajištění potravin; Institutional structure; Biodiversity